Making state circular economy parks work for Indian states (Part 1): An emerging story of Rajasthan - Amrita Goldar; Tarun; Malay Kotal; Ritika Verma (Indian Council for Research on International Economic Relations (ICRIER), 2024)
As global e-waste streams rise, recycling efforts remain insufficient, as does the willingness to promote recycling. This insufficiency is primarily due to the perception of "waste" as "disposable", which has hindered its consideration as a business opportunity. Over time, this perception has negatively impacted the development of the recycling sector. To counter this prevailing notion, this working paper promotes the idea of "e-waste as a commodity" and argues that recycling can stimulate economic growth and support the primary supply of critical minerals used in manufacturing electronic equipment. Acknowledging the potential impact of e-waste, it is necessary to recycle it to minimize loss and maximize profit. To achieve this, the working paper proposes and evaluates the concept of e-waste-focused industrial parks called "E-Waste Recycling Parks" or ERPs. This concept is an extension of eco-industrial parks and aims to boost the recycling industry, making the recycling business more economically viable. Furthermore, the paper develops a framework outlining five critical factors for the development of ERPs in India. These factors include understanding the demand for ERPs, reviewing legislative and regulatory frameworks, financing and operationalizing ERPs, and post-establishment monitoring. In India, several states increasingly acknowledge the concept of ERPs, including Maharashtra, Rajasthan, and Delhi. This working paper focuses on the state of Rajasthan and details how the state plans to implement a recycling project within a waste recycling park. The paper explains how factors such as waste flow dynamics, the location of the park, and other elements can be leveraged to benefit the recycling park.
Keywords: Q53; Q58; R58; 330; E-Waste; E-waste Recycling Park (ERP); Regional analysis